Massiveness of Exceptional Sets of Multi-Term Asymptotic Representations of Subharmonic Functions in the Plane - Agranovich, P. (Журнал математической физики, анализа, геометрии, 2006)
It was investigated the massiveness of exceptional sets that arise in multiterm asymptotic representations of subharmonic functions.